The history of computers [ (Video Education Australasia, 2006)
The program traces the development of the electronic computer, from the first valve-based devices of the mid 20th century, to the invention of silicon-based technology leading to the manufacture of the first PCs. The constant phenomenal growth in computing power and speed, with reduction in costs, are central themes. The program finishes by examining what the future might hold in relation to computing technologies